A Structural Equation Model for Enhancing Online Brand Community Loyalty - Limpasirisuwan, Natcha; Donkwa, Kwunkamol (The Journal of Behavioral Science, 2017)
Online brand communities are an important tool for creating market opportunities. Previous studies have concluded that they generate value for their brands, yet little is known about how to manage them in order to secure the loyalty of their members. The current study aims to test a model of members’ loyalty to online brand communities and to study the impact of the perceived values on members’ loyalty through mediator variables which include community satisfaction and community trust. The samples obtained are active participants of Facebook fan pages for automobile brands in Thailand. The sample size was 512 respondents obtained by using a systematic random sampling technique. An online questionnaire was used to collect data, which were analyzed by means of structural equation modeling. The results show that the model fits the empirical data, considering goodness of fit measures, namely Chi-square = 44.761 (df = 20), p-value = 0.001, (χ2/df) = 2.24, CFI = 0.995, TLI = 0.985, RMSEA = 0.048, and SRMR = 0.018. The perceived value factors were important for the enhancement of members’ satisfaction with online brand communities. A high degree of member satisfaction with online brand communities resulted in a greater trust in the communities. Moreover, the members’ loyalty was influenced by their satisfaction, but not by their trust. Therefore, the results of this study suggest that the administrators of online brand communities encourage the members’ satisfaction by creating brand contents. These lead to high member loyalty by positive communication intention with others. Keywords: online brand community, perceived value, satisfaction, trust, loyalty